PENGARUH LATIHAN INTERVAL TRAINING TERHADAP KECEPATAN LARI DALAM PERMAINAN PADA TIM PUTRI SMK NEGERI 3 DUMAI - Sudi Harto; Zainur Zainur; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this research is that there is still a shortage in the women's indoor soccer team at SMK Negeri 3 Dumai, when they dribble they can't pass the opponents because they don't have the speed to run away from the opponent or when they are going to grab the ball of the opponent. The aim of this study was to determine the effect of Intrval Training exercises on walking speed on the indoor soccer team of Putri SMK Negeri 3 Dumai. The site of this research was conducted in the area of the SMK Negeri 3 Dumai school. The survey was conducted from September 2019 to December 2019. The sample used in this survey consisted of 10 Putri SMK Negeri 3 Dumai futsal players. Because the study uses one group, this study uses a design approach for pre-test post-test with one group. In this design, there is a pre-test before treatment. Based on the analysis of the pre-test and post-test data, there was an increase of 2.95 seconds and based on the statistical analysis of inference using the t-test resulted in a tcount of 6,704 greater than the table of 1,833. Means tcount> ttable So it can be concluded that the given Interval Training has a positive influence on walking speed. Based on the results of the analysis, it was concluded that there was an influence of interval training on walking speed on the indoor soccer team of Putri SMK Negeri 3 Dumai. Key Words: Interval training Practice, Running Speed